(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2004)
In the United States, collective bargaining plays such an important role in the establishment of labor relation guidelines that it goes above and beyond the law. It is limited, however, by the duty to act in good faith. Due to the reference of this duty in the new Civil Code, this concept is worthy of consideration today in Brazil.